Comparative Assessment of Commonly Used Concrete Damage Plasticity Material Parameters - AL-RIFAIE, Hasan; MOHAMMED, Darbaz (Engineering Transactions, 2022)
The non-homogeneous and non-linear mechanical behaviour of concrete complicates the numerical simulations of its corresponding material model. The concrete damaged plasticity (CDP) model is one of the most popular constitutive models for concrete. State-of-the-art CDP material parameters are introduced in Abaqus documentation [1], Jankowiak and Łodygowski [2], and Hafezolghorani et al. [3]. Accordingly, this paper presents a novel comparative study of these commonly-used concrete CDP parameters by assessing the response of plain concrete specimens under quasi-static loading conditions. The research conducts standard laboratory tests: compressive strength test of a concrete cube and three-point flexural test of a plain concrete beam. Sophisticated non-linear computational models are built using Abaqus/CAE and analysed using Abaqus/Explicit solver. The results discuss and compare deformations, damage patterns, reaction forces, compressive strength, tensile stress and modulus of rapture. The thorough study concludes that choosing CDP parameters is case-dependant and should be selected carefully.